Princess Milica – the Sacralisation of Queenship, Official Sanctity and National Myth - Brzozowska, Zofia (Poznańskie Studia Slawistyczne, 2013)
This article is devoted to the one of the best known female rulers of medieval Serbia – princess Milica, wife of the prince Lazar Hrebeljanović, who had lost his live during the famous Battle of Kosovo Field in 1389. After the death of her husband, Milica founded the Ljubostinja monastery and became the nun Jevgenija. She was a close friend to the famous Serbian poet Jefimija, who accompanied princess Milica in the diplomatic mission to the Sultan’s court in 1398/1399. She died in 1405. She was canonized by the Serbian Orthodox Church. She appears also – as „tsaritsa Milica” – in Serbian folklore (epic poetry).